Biofortiﬁcation with copper in green wheat forage - Antonio-Medina, Anadelia; Gaytán-Alemán, Leticia Romana; Nava-Camberos, Urbano; Mendoza-Pedroza, Sergio Iban; Veliz-Deras, Francisco Gerardo; Arellano-Rodríguez, Gerardo (Ecosistemas y Recursos Agropecuarios, 2022)
Due to the importance of minerals in nutrition, it was decided to evaluate the accumulation of copper (Cu) in the hydroponic green forage of wheat (FVH) in different solutions and modiﬁcations in the pH. A completely random factorial arrangement of 3 x 4 x 3 with three repetitions was used. Each tray represented an experimental unit, the study factors were three different solutions, four copper treatments and three pH levels; factor A, tap water (ALl), nutrient solution (SN) (Steiner’s method) with distilled water (AD) and nutrient solution (SN) with tap water (ALl); factor B, products of Cu (4, 1.3, 0.2 and 25%) and factor  C pH (5.0, 6.0 and 7.8). The variables evaluated were: copper content and bromatological analysis. The results were subjected to an analysis of variance and the mean  eparations were carried out using the Tukey test (α ± 0.05). There was a greater absorption of copper in the interaction of tap water (ALl) with respect to fertilizer (F) in concentration of 1.30% Cu-EDTA presenting a concentration of 5.51 ppm, and in the solutions of distilled water (AD) with nutritive solution (SN) and pH 6 showing an absorption of 3.94 ppm. The copper content in the forage modiﬁed FDA and FDN, these results may be useful in future studies to carry out more tests on the biochemical characteristics related to forage digestibility, and in biofortiﬁcation.